EMPOWERING COASTAL COMMUNITIES THROUGH COMMUNITY-BASED TOURISM: A CASE STUDY OF MUARA GEMBONG WITH A FOCUS ON PANTAI BAHAGIA, INDONESIA THROUGH THE PENTA HELIX LENS - Jason Adinata Wijaya; Tony Kristhiofan; Felix Goenadhi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2025)
This study explores the potential of Muara Gembong, a coastal sub-district in Bekasi Regency, West Java, to develop sustainable tourism through a Community-Based Tourism (CBT) approach supported by the Pentahelix model. Faced with environmental degradation, tidal flooding, and declining fisheries, the region seeks alternative pathways for socio-economic resilience. Using qualitative methods such as field observations, interviews, focus group discussions, and participatory co-design sessions, this research highlights the key roles played by the local KEBAYA community, private sector partners, and academic institutions in designing tourism experiences rooted in local culture and ecology. The findings reveal significant opportunities for mangrove ecotourism, culinary heritage-based tourism, and craft-based activities like natural-dye batik making. However, persistent challenges such as poor infrastructure, weak governance, limited market access, and unequal stakeholder dynamics hinder progress. The study concludes that integrated stakeholder collaboration, policy recognition, capacity-building, and formalized community ownership structures are essential to transform Muara Gembong into a model of inclusive and sustainable rural tourism.